Simplified FE-Based Post-Earthquake Vulnerability Assessment of a Partially Collapsed Historic Mosque - Rüya Kılıç Demircan (Buildings)
On 6 February 2023, two major earthquakes struck southeastern Türkiye along the East Anatolian Fault, causing widespread structural damage, including the partial collapse of the historic Habibi Neccar Mosque in Antakya. This study presents a simulation-based approach to rapidly assess the seismic vulnerability of this partially damaged historic masonry structure. Due to the complexity and urgent condition of such heritage buildings, a simplified finite element (FE) modeling methodology is employed to evaluate structural behavior and support immediate stabilization decisions. Response spectrum analysis is applied to simulate and interpret stress distribution and deformation patterns in both undamaged and damaged states. The simulation results highlight significant tensile stress concentrations exceeding 0.2 MPa at dome–arch joints and vaults—primary indicators of localized failures. Additionally, the analysis reveals increased out-of-plane deformations and the influence of soil amplification in the remaining walls, both of which further compromise the structural integrity of the building. The findings demonstrate that simplified FE simulations can serve as practical and efficient tools for early seismic assessment of historic structures, contributing to rapid decision making, risk mitigation, and cultural heritage preservation in earthquake-prone areas.